How Social Reproduction Shapes Women’s Union Militancy - Mariela Cambiasso (Global Labour Journal)
Feminist scholarship has long examined how capitalism forces working women to shoulder the bulk of social reproduction. This remains a widely discussed topic in academic and political debates today, encouraged by the effects of the crisis of neoliberal capitalism that particularly hits working-class women, an observation Nancy Fraser (2016) deepens with the notion of a “crisis of social reproduction”. The effects of this dynamic on the union and political militancy of women have also been discussed at length. Still, this topic remains relevant and pressing, especially when examining its impact on union organisations. If the intention is to broaden the participation of women workers in union activities, we must dispense with attitudes that remain hostile to their militancy.